Studi komparasi analisis normatif antara metode cipw dengan metode pemrograman linear (lpnorm)= (A Comparative study of norm analyses between CIPW and Linear Programming (LPNORM) methods) - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran(UI2P2) UGM, 2005)
ABSTRACT The norm' analyses for igneous, sedimentary and metamorphic rocks are performed to calculate the mineral composition of mostly fine-grained rocks, such as volcanic rocks, pelitic sediment (clay, silt and shale), and metamorphic rocks (slate and f?hYllite). However, the course-grained rocks are also possible, especially for volume-percent calculation of mineral composition in the rocks. The comparative study between CIPW norm and LPNORM shows slightly different results. Plagioclase, pyroxene, ilmenite and apatite minerals have a consistent result in both CIPW and LPNORM. Orthoclase, olivine and magnetite minerals are rised in CIPW norm, whereas biotite can only be calculted by LPNORM. The different results of these methods are because of different basic principles of both methods. The CIPW norm can be used only for .water-free standard minerals (anhydrous minerals) or assumed as anhydrous rocks, whereas LPNORM, which is based on linear optimization, can be used both hydrous and anhydrous rocks. Both methods has disadvantage to determine glass volcanic content in the volcanic rocks. Thus, a combination of CIPW, LPNORM and petrography will give mineral compotion more representative Keywords: Analisis normatif, Metode CIPW, pemograman linear